Outcomes after radical endoscopic resection of high risk T1 esophageal adenocarcinoma: an international multicenter retrospective cohort study - Chan, Man Wai; Haidry, Rehan; Norton, Benjamin; di Pietro, Massimiliano; Hadjinicolaou, Andreas V.; Barret, Maximilien; Doumbe Mandengue, Paul; Seewald, Stefan; Bisschops, Raf; Nafteux, Philippe; Bourke, Michael J.; Gupta, Sunil; Mundre, Pradeep; Lemmers, Arnaud; Vuckovic, Clémence; Pech, Oliver; Leclercq, Philippe; Coron, Emmanuel; Meijer, Sybren L.; Bergman, Jacques J. G. H. M.; Pouw, Roos E. (Endoscopy, 2025)
Post-endoscopic resection (ER) management of high risk T1 esophageal adenocarcinoma (EAC) is debated, with conflicting reports on lymph node metastasis (LNM). We aimed to assess outcomes following radical ER for high risk T1 EAC.We identified patients who underwent radical ER (tumor-negative deep margin) of high risk T1 EAC, followed by surgery or endoscopic surveillance, between 2008 and 2019 across 11 international centers.106 patients (86 men; mean [SD] age, 70 [11] years) were included. Of these, 26 (age, 64 [11] years) underwent additional surgery, with residual T1 EAC found in five patients (19%) and LNM in two (8%). After a median [IQR] follow-up of 47 [32–79] months, 2/26 patients (8%) developed LNM/distant metastasis, with one EAC-related death (4%), one unrelated death (4%), and four patients lost to follow-up (15%). Of the 80 patients (age, 71 [9] years) who entered endoscopic surveillance, 5/80 (6%) developed LNM/distant metastasis, with four EAC-related deaths (5%) over 46 (IQR 25–59) months follow-up; there were 15 unrelated deaths (19%), and 10 patients lost to follow-up (13%). The overall rates (95%CI) were: LNM, 6% (2%–12%); LNM/distant metastasis, 7% (3%–13%); EAC-related mortality, 5% (2%–11%); overall mortality, 20% (95%CI 13–29).Our findings present low rates of LNM after radical ER of high risk T1 EAC, consistent with other endoscopy-focused studies. Post-surgical patients are still at risk for metastasis and disease-specific mortality. These results suggest that endoscopic surveillance is suitable for selected cases, but further prospective studies are needed to refine patient selection and confirm optimal outcomes.